The role of social support in the process of cardiologic rehabilitation - Mróz, Justyna (Polish Journal of Public Health, 2010)
Introduction. The issue of social support has been examined for years as far as the influence of psychosocial variable on health condition and functioning during the illness is concerned. Social support is one of the variables preventing negative effects of stress or reducing its negative influence on people’s lives. Aim. The aim of this research was to define the relationship between the social support experienced and the level of emotional well-being in distinguished periods of time in patients after myocardial infarction. Material and methods. One hundred and thirteen people after a myocardial infarction took part in the research. The research tools used in the study were: Scale of Social Support by K. Kmiecik-Baran and the Scale of Emotions and Feelings Existentially Relevant by K. Popielski. Results. Social support correlates essentially with all the components of emotional well-being in specified periods of time. It correlates favourably with the positive affect and affective balance, whereas it correlates adversely with the negative affect and affective stimulation. Conclusions. The results of the research indicate the need for permanent training and support for the medical staff; the need to create supportive groups not only for ill people but also for their families and relatives. Well prepared staff can provide the necessary support – informative and emotional alike.